2013
DOI: 10.1037/a0030309
|View full text |Cite
|
Sign up to set email alerts
|

Online harassment in context: Trends from three Youth Internet Safety Surveys (2000, 2005, 2010).

Abstract: The increase in youth online harassment from 6% in 2000 to 11% in 2010 was driven primarily by a rise in indirect harassment-someone posting or sending comments to others about them online. Girls made up an increasing proportion of victims: 69% of victims were girls in 2010 compared with 48% in 2000. Furthermore, in comparison with earlier in the decade, harassment incidents in 2010 were more likely to come from a school friend or acquaintance and occur on a social networking site. Victims reported disclosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
1
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(127 citation statements)
references
References 34 publications
4
110
1
12
Order By: Relevance
“…Given the age group of victims within this sample and the potential for offenders to tailor their grooming style to fit what they know of the victims; the results are discussed in the context of grooming adolescents (rather than children). This study cannot make inferences about the prevalence of online grooming, but while recent US research suggests that online sexual solicitations are in fact decreasing [26] and most forms of harassment online actually come from peers [27], the current study highlights that online grooming by adults remains an issue requiring greater understanding. Existing literature recognizes grooming others can be a phase within the grooming process [7,20,28], and this is apparent through many of the victims' experiences within this study.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Given the age group of victims within this sample and the potential for offenders to tailor their grooming style to fit what they know of the victims; the results are discussed in the context of grooming adolescents (rather than children). This study cannot make inferences about the prevalence of online grooming, but while recent US research suggests that online sexual solicitations are in fact decreasing [26] and most forms of harassment online actually come from peers [27], the current study highlights that online grooming by adults remains an issue requiring greater understanding. Existing literature recognizes grooming others can be a phase within the grooming process [7,20,28], and this is apparent through many of the victims' experiences within this study.…”
Section: Discussionmentioning
confidence: 57%
“…Despite current research suggesting that disclosure rates are increasing [27], all cases of grooming in this study only ended due to someone reporting on behalf of the victims or the offender getting caught as part of a wider police investigation. This lack of victim suspicion is likely to be associated with the parallels between the offenders' grooming techniques and typical adolescent peer relationships, but also demonstrates the extent to which victims had been groomed.…”
Section: Implications Of This Researchmentioning
confidence: 80%
“…Findings from the WHO survey (Currie et al, 2012) indicated an overall decline in peer victimization in most countries over previous years, although the decline was small, usually less than 10% (see also Rigby & Smith, 2011). In the United States, youth reports of physical bullying declined from 22% in 2003 to 15% in 2008 (Finkelhor, Turner, Ormrod, & Hamby, 2010), but online harassment increased from 6% in 2000 to 11% in 2010 (Jones, Mitchell, & Finkelhor, 2013). Thus, although traditional forms of bullying may be declining, cyberbullying appears to be on the rise as access to technology becomes more ubiquitous.…”
Section: Shelley Hymelmentioning
confidence: 99%
“…Here, hate victimization refers to experiences of being personally targeted by such content online. Harassment victimization, on the other hand, refers to experiences of being directly targeted online by broader social abuse or misrepresentation which resemble forms of offline peer victimization, such as bullying, that can be motivated by factors other than racism or xenophobia (Jones, Mitchell, & Finkelhor, 2013;Näsi et al, 2014;Priebe & Svedin, 2012;Ybarra & Mitchell, 2004).…”
Section: Research-article2017mentioning
confidence: 99%